2013
DOI: 10.5539/ies.v6n2p110
|View full text |Cite
|
Sign up to set email alerts
|

“Playing With Words”: Effects of an Anagram Solving Game-Like Application for Primary Education Students

Abstract: The present study reports the basic characteristics of a game-like application entitled "Playing with WordsPwW". PwW is a single-user application where a word must be guessed given an anagram of that word. Anagrams are presented from a predefined word list and users can repeatedly try to guess the word, from which the anagram is derived, by placing (drag & drop) successively the given letters into the correct orthotactic order. Each effort is assessed as either correct or incorrect, while reaction and total ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a previous study in the Greek language, reading fluency was found to share strong correlation to performance on anagram solving tasks (Panagiotakopoulos & Sarris, 2013). Following up on this issue, we examined the association between reading fluency and the linguistic factors of syllabic structure and graphemic frequency by comparing the number of moves required to solve the anagrams.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In a previous study in the Greek language, reading fluency was found to share strong correlation to performance on anagram solving tasks (Panagiotakopoulos & Sarris, 2013). Following up on this issue, we examined the association between reading fluency and the linguistic factors of syllabic structure and graphemic frequency by comparing the number of moves required to solve the anagrams.…”
Section: Resultsmentioning
confidence: 97%
“…As Henin and his collaborators (2009, p. 906) argue, anagram solution is "… an extension of natural word-reading ability, which is highly sensitive to structural knowledge of the language and is generally agreed to involve parallel processing in skilled readers". In a recent study (Panagiotakopoulos & Sarris, 2013), performance on anagram solving tasks was found to share significant correlation to reading fluency measures. In fact, children's performance on anagram solution tasks explained 30% of the variance in reading fluency.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…An anagram is a game that forms a word by rearranging the letters of another word [1]. The main purpose of anagrams is to form correct words according to the spelling system of a language [2]. One of the innovations that have been developed in anagram games is the gameplay, where players must be able to compose anagram and sub-anagram words to attack enemies [3].…”
Section: Introductionmentioning
confidence: 99%